1,25 dihydroxyvitamin D dan kalsium pada akseptor depot medroxyprogesteron asetat (DMPA) berdasarkan lama pemakaian - Netti Meilani Simanjuntak; Eti Yerizel; Yusrawati Yusrawati (Jurnal Gizi Klinik Indonesia, 2018)
Background: Long – term usage of depot medroxyprogesterone acetate (DMPA) may suppress estrogen levels causing the body to undergo hypoestrogenic. The hormone estrogen affects the metabolism of calcium and 1,25 dihydroxy vitamin D in the body. Calcium and 1,25 dihydroxy vitamin D are bone-forming vitamin and minerals.Objective: This study aimed to analyze the relationship between 1,25 dihydroxy vitamin D and calcium on the accelerate of DMPA based on long usage.Method: This is an observational study with cross-sectional design. A total of 70 acceporates sample was chosen by consecutive sampling and divided into 2 groups. 35 acceporates received DMPA for 1-2 years (group 1) and 35 acceporates received DMPA for 2-4 years (group 2). Serum 1,25 dihydroxy vitamin D levels examined by enzyme-linked immunoabsorbent assay (ELISA) method and serum calcium was quantified using the Calcium Arsenazo method. The research was conducted in Puskesmas Andalas and Lubuk Buaya Kota Padang between July 2017 and September 2017. The data normality was checked using Kolmogorov Smirnov and then the data were analyzed using the Spearman test.Results: The average of 1,25 dihydroxy vitamin D in group 1 is 351.16 pg/ml and in group 2 is 289.84 pg/ml. The median concentration of calcium on samples in group 1 is 9.30 mg/dl and in Group 2 is 9.13 mg/dl.Conclusion: There were negative significant correlations between 1,25 dihydroxy vitamin D and calcium in group 1 and group 2.